Relieve Labor Pain With Hypno Prenatal and Prenatal Yoga - Yunetra Franciska; Aprillia Ayu Shinta Yuka; Wilma Wilma (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Pregnancy and childbirth are physiological processes that every woman will go through. The intensity of pain experienced by women during labor varies, but it can be exacerbated by fear, tension, and anxiety. Hypnosis techniques have been proposed as a means of overcoming anxiety and fear. Compared to women who receive relaxation training or supportive counselling, hypnosis reduces pain intensity, shortens delivery time, and reduces the number of women who stay in the hospital for more than two days after their baby is born. Yoga during pregnancy, like hypnosis, has been shown to reduce pain intensity during the first stage of labor. This research aimed to see how prenatal hypnosis and prenatal yoga affected labor pain in women giving birth at the Independent Practice of Midwife Meli Rosita Palembang. This study employs an experimental research design with a Static Group Comparison strategy. The sample in this study consisted of 60 pregnant women divided into two groups: those who received hypnosis and prenatal yoga interventions and those who did not. Questionnaires, checklists, and tutorials on implementing prenatal hypnosis and prenatal yoga were used as instruments. Prenatal hypnosis and prenatal yoga significantly affected labor pain in Maternal Maternity at Meli Rosita's Independent Midwife Practice (p-value 0.000). The intervention group had a pain scale average of 2.70, while the control group had a pain scale average of 4.33. As a result, a combination of prenatal hypnosis and prenatal yoga can alleviate labor pain.